Enhanced Thermostability, Thermo‐Optics, and Thermomechanical Properties of Barium Gallo‐Germanium Oxyfluoride Glasses and Glass‐Ceramics. Issue 8 (12th July 2013) - Zhang, Shaoqian; Xu, Mingxiu; Chen, Xi; Zhang, Yuelong; Calvez, Laurant; Zhang, Xianghua; Xu, Yinsheng; Huai, Ying; Jin, Yuqi; Ballato, J.
<x xml:space="preserve">Abstract</x> Serial substitutions of BaF2 for BaO in BaO–Ga2O3–GeO2 glasses were performed, and the effects of the substitutions on the glass properties were investigated. The glass transition temperature, density, refractive index, thermo‐optics coefficient, and figure of merit for thermal shock decreased with the replacement of oxygen by fluorine. On the other hand, the glass‐forming ability increased. Fluorine substitution removed the absorption band of hydroxyl near 2.9 μm. Raman scattering spectroscopy was used to characterize the fluorogermanate glasses. The crystallization process of the glass‐ceramics under different heat‐treatment conditions was also investigated using differential scanning calorimetry, X‐ray diffraction, scanning electron microscopy, and atomic force microscopy. The thermal and mechanical properties were improved by controlling the crystal size of the near‐ and middle‐infrared transparent glass‐ceramics.